ANALISIS FENOMENA JANUARY EFFECT PADA SAHAM SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Indrayani Indrayani (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
This study aims to analyze the January Effect phenomenon based on the presence or absence of significant difference between the 5-days average abnormal return in the end of December and 5 days in early January on mining stocks listed on the Indonesia Stock Exchange during the period 2011-2015. The January effect is the tendency of rising stock prices between 31 December to the end of the first week in January. The population of this study is 41 companies and the samples are 35 companies taken using purposive sampling technique. The data used are secondary data in the price of the daily closing of stocks and JCI during the observation period. Data analysis method used is descriptive statistical analysis. The hypothesis testing is conducted using non-parametric difference test which is called as WilcoxonSigned Rank Test. The results showed that there is a significant difference between the 5-days average abnormal return in the end of December and 5 days in early January on mining stocks listed on the Indonesia Stock Exchange during the period 2011-2015, so the January Effect phenomenon has occurred.